Effects of clonal integration on allelopathy of invasive plant Wedelia trilobata under heterogeneous light conditions. (31st March 2021) - Pu, Lei; Cheng, Lang; Li, Ai; Liang, Sha; Wei, Qing; Wu, Shulan; He, Linxuan; Xu, Xiangning; Lei, Ningfei; Chen, Jinsong
Abstract: Plant invasion is one of the most serious threats to ecosystems worldwide. When invasive plants with the ability of clonal growth invading or colonizing in new habitat, their interconnected ramets may suffer from heterogeneous light. Effects of clonal integration on allelopathy of invasive plants are poorly understood under heterogeneous light conditions. To investigate the effects of clonal integration on allelopathy of invasive plant Wedelia trilobata under heterogeneous light conditions, a pot experiment was conducted by using its clonal fragments with two successive ramets. The older ramets were exposed to full light, whereas the younger ones were subjected to 20% full light. The younger ramets of each clonal fragment were adjacently grown with a target plant (one tomato seedling) in a pot. Stolon between two successive ramets was either severed or retained intact. In addition, two tomato seedlings (one as target plant) were adjacently grown in a pot as contrast. Compared with severing stolon, biomass accumulation, foliar chlorophyll and nitrogen contents, chlorophyll fluorescence parameters and net photosynthetic rates of the target plants as well as their root length and activity, were significantly decreased when stolon between interconnected ramets of W. trilobata retained intact. Under heterogeneous light conditions, transportation or sharing of carbohydrate between two successive ramets enhanced allelopathy of the young ramets subjected to 20% full light treatment. It is suggested that clonal integration may be important for invasion or colonization of invasive plants with ability of clonal growth under heterogeneous light conditions.